THE EFFECTIVENESS OF DEEP BREATHING AND SLOW STROKE BACK MASSAGE TO DECREASE THE BLOOD PRESSURE ON A PATIENT WITH HYPERTENSION - Maria Anita Yusiana; Heru Suwardianto (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2014)
Introduction: Many patients with hypertension have not got the proper treatment in controlling blood pressure (BP). The purpose of this study was to analyze the effectiveness of deep breathing (DB) and slow-stroke back massage (SSBM) in BP reduction to patients with hypertension. Method: The design was a True Experiment the Solomon Three-Group Design. Sampling technique was group randomized plan as many as 60 people. The treatment given was BP and SSBM. Blood pressure data retrieval used mercury spigmomanometer. Results: The results were ρ of BP values (systolic) was 0,000, while the value of ρ (diastolic) was 0,000. The value ρ of SSBM (systolic) was 0.000 while the value of ρ (diastolic) was 0.001. The statistical results of the effectiveness BP systolic reduction was the significant difference in both interventions with a control group with ρ = 0.000 and the most effective was the DB compare to SSBM with ρ = 0.05 (4.0 mmHg). While there are differences in BP diastolic reduction significantly in both interventions with the control group with ρ = 0.000 and the most effective was DB than SSBM with ρ = 0.01 (6.6 mmHg). Discussion: It can be concluded DB and SSBM are effective to lower BP (systolic mean difference of 9.3 mm Hg of DB and SSBM 5.3 mmHg, while diastolic mean DB 11.2 mmHg and SSBM. Keywords: deep breathing, slow stroke back massage, blood pressure, hypertension